Laparoscopic cholecystectomy and common bile duct exploration using choledochotomy and primary closure following failed endoscopic retrograde cholangiopancreatography: A multicentric comparative study using three-port vs multiport (2020)
Background: Laparoscopic surgery has changed many ways in which we as surgeons manage patients, offering better results, quicker recovery, and fewer complications using minimally invasive techniques, especially in common bile duct (CBD) surgery. Not only can laparoscopic techniques be applied to programed surgery but also emergencies and those following failed endoscopic retrograde cholangiopancreatography (ERCP). Objectives and aims: Describe and compare clinical and surgical results of the laparoscopic CBD exploration with primary closure using a 3-port vs multiport approach. Materials and methods: We present a multicentric comparative study of 197 consecutive patients who underwent a laparoscopic gallbladder removal along with CBD exploration with primary closure following failed (ERCP to extract CBD stones; 104 patients were managed by three-port vs 93 multiport laparoscopic surgery in five centers of Bogotá, Colombia, between 2013 and 2017 with follow-up of 1 year. Results: A total of 197 patients were taken to laparoscopic gallbladder removal along with CBD exploration with primary closure, 104 patients via three-port technique and 93 patients via multiport. All (100%) the patients had previously failed ERCP. The average surgical time on the three-port approach was 106 minutes vs 123 minutes on multiport. Only in the multiport technique we had an average conversion of 2%. Mean hospital stay of 2.5 days, less for the three-port approach vs multiport in 5–7 days. There was a need of reintervention in 1% of the patients who underwent three-port exploration. Conclusion: Postoperative pain, use of an additional port, complication rates, operation time, and cost of the three-port technique were similar to those of the conventional approach. Large randomized controlled trials are needed to examine the true benefits of the three-port technique.